The N-Methyl-D-Aspartate Receptor in Cerebral Ischemia - Tan, Terence; Albert, PhD, Mitchell; Sun, PhD, Yanpi (North American Journal of Medicine and Science, 2009)
Excitotoxicity is a major mechanism of neuronal damage in cerebral ischemia and is mediated largely by neuronal N-methyl-D-aspartate receptors (NMDAR). This review presents the structural and functional alterations in NMDAR after an ischemic insult, including the antagonistic roles different NMDAR sub-types play in the post-ischemic period. By elucidating these molecular changes and the effects they have on downstream cellular signaling, rational therapy can be devised in an attempt to mitigate the effects of cerebral ischemia.